A Flora of Southern Illinois - Mohlenbrock, Robert H., 1931- (Book collections on Project MUSE., 1974)
This book will be of particular interest to those interested in applied fields of biology, such as conservation, forestry, and wild life. The southern twelve counties of Illinois, a total of 4,355 square miles, comprise the area covered in this book. It is an area in which both northern and southern flora specimens abound. A wide variety of plant species grow in this area, and nearly 200 new plants not formerly identified with this area have been included in the listings. Especially valuable to amateur botanists, the book is an important manual in identifying.